Membangun Kesadaran Keislaman Melalui Pendekatan Syariat dan Tarekat: Pemberdayaan Komunitas Yayasan Mukti Jaya - Nurjanah; Sudarman; Sobirin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The challenge of Islamic awareness in the modern era lies not only in the lack of participation in religious activities but also in the fragmented understanding between sharia (legal aspect) and tarekat (spiritual dimension). This Community Service Program (PKM) aims to foster comprehensive Islamic understanding within the Mukti Jaya Foundation community in Bekasi through an integrative approach that combines syariah and tarekat. The method consisted of interactive seminars, spiritual discussions, and guidance, involving 20 participants from the foundation’s board, students, parents, and the surrounding community. The activity was conducted in three stages: preparation, implementation, and evaluation. Evaluations were carried out using questionnaires and participatory observation. The results showed that 90% of participants improved their understanding of syariah and tarekat, 85% expressed interest in attending future study sessions, and there was a 30% increase in religious participation. These findings indicate that a moderate spiritual approach based on tarekat can enhance community solidarity, social ethics, and individual Islamic practice. This program recommends regular study forums, youth involvement, and the development of digital dakwah media. In conclusion, the integration of syariah and tarekat is an effective strategy for developing holistic Islamic awareness at the community level.